Efektivitas Intervensi Kelompok Daring Berbasis CBT dalam Meningkatkan Pengelolaan Marah pada Remaja SMP - Vanda Pebruarini; Efriyani Djuwita (Universitas Andalas, 2023)
Anger management is known to be challenging for adolescents because they often lack experience or coping skills to cope with complex emotions. Intense anger or unassertive anger expression may inflict severe problems on their social, physical, and mental health. This study aims to assess the effectiveness of Cognitive Behavior Therapy (CBT) based online intervention in improving anger management skills in four junior high school students. This mixed method research with the qualitative and quantitative results. The participants of this study are 12 – 15 years old with a high level of anger. The result showed that all participant level of anger decreased significantly, also their anger expression. Participants' anger management also increased significantly compare to the post-test and follow-up test (1-month interval). The qualitative result showed that all participants expressed that their anger management improved after the session. In conclusion, this online CBT proved to be effective in reducing adolescent anger levels and expression and increasing their anger management ability.